A Randomized, Open-Label Study Conducted to Evaluate the Bioequivalence of Pegfilgrastim-cbqv On-Body Injector Versus Prefilled Syringe in Healthy Male Participants - Tang, Hong; Civoli, Francesca; Tatarewicz, Suzanna; Vandenkoornhuyse, Nathalie; Finck, Barbara (Advances in therapy, 2024)
Introduction To help prevent febrile neutropenia, pegfilgrastim-cbqv (UDENYCA ® ; Coherus BioSciences), a pegfilgrastim (NEULASTA ® ; Amgen) biosimilar, is administered 24–96 h after myelosuppressive chemotherapy. Delivery of pegfilgrastim-cbqv using an on-body injector (OBI) provides an alternative method of administration, affording options in drug delivery. This study aimed to establish pharmacokinetic (PK) and pharmacodynamic (PD) bioequivalence and assess the safety of pegfilgrastim-cbqv administered using an OBI compared with a prefilled syringe (PFS). Methods In this open-label, two-period crossover study, healthy adult male participants ( N = 189) were randomly assigned 1:1 to receive pegfilgrastim-cbqv 6 mg subcutaneously using an OBI ( n = 92) or a PFS ( n = 95) in period 1 and then an injection via the other method in period 2. Primary PK end points were area under the concentration–time curve from time 0 to infinity, area under the concentration–time curve from time 0 to the last quantifiable concentration, and maximum plasma concentration. Secondary PD end points, safety, immunogenicity, and tolerability were also assessed. Results The 90% confidence intervals (CIs) of the geometric mean ratios for the PK and PD end points fell within the predetermined range (80–125%), indicating PK and PD bioequivalence between pegfilgrastim-cbqv OBI and pegfilgrastim-cbqv PFS. Treatment-emergent adverse events (TEAEs) occurred in 87.8% and 75.8% of participants in the OBI and PFS groups, respectively. Most TEAEs were musculoskeletal effects. The most common OBI-related TEAE was injection site erythema (31.7%), which was mild, transient, and self-limiting. The incidence of treatment-emergent antidrug antibodies (ADAs) was similar between the OBI and PFS. ADAs had no apparent impact on PK, PD, or safety. Neutralizing antibodies were not detected in any participant. Conclusions Results of the study showed PK and PD bioequivalence of pegfilgrastim-cbqv administered using OBI compared with PFS. OBI and PFS administration had similar safety, tolerability, and immunogenicity profiles. No unexpected safety signals were identified. Graphical Abstract available for this article. Graphical Abstract Plain Language Summary Febrile neutropenia is when a patient has a fever and a lower-than-normal number of white blood cells. When white blood cell counts are low, patients are more susceptible to opportunistic infections as a result of their weakened immune systems. Severe febrile neutropenia can lead to the stopping or delaying of chemotherapy. The drug pegfilgrastim-cbqv is used 24–96 h after chemotherapy to stimulate the growth of white blood cells. Pegfilgrastim-cbqv is available in a single-dose prefilled syringe and in a prefilled autoinjector. If a patient cannot inject themselves with the drug, they must go to a clinic for the injection. Using an on-body injector applied to the skin that automatically injects the drug at a specific time could eliminate the need to go to the clinic. During this study, healthy adult male participants were given pegfilgrastim-cbqv through an on-body injector or a prefilled syringe to investigate if the movement of the drug into, through, and out of the body (pharmacokinetics) and the physiological action of the drug in the body (pharmacodynamics) were similar between the two injection methods. Side effects were also studied. The researchers found that the pharmacokinetics and pharmacodynamics for pegfilgrastim-cbqv given by on-body-injector or prefilled syringe were similar. The number and types of side effects were also similar. The most common side effect for the on-body injector was mild erythema at the injection site. This side effect resolved by itself. The treatment benefit and safety of pegfilgrastim-cbqv were very similar regardless of how the drug was administered.